Sejarah Melayu - Rajantheran, M. (Dewan Bahasa dan Pustaka, 1999)
History of relations between the Malay archipelago and India; criticism of the Malay literary classic Sejarah Melayu
Keywords: Melaka (Sultanate); History; Malaya; India